The effects of obesity on oesophageal function, acid exposure and the symptoms of gastro‐oesophageal reflux disease. Issue 5 (10th January 2013) - Anggiansah, R.; Sweis, R.; Anggiansah, A.; Wong, T.; Cooper, D.; Fox, M.
Summary Background Obese patients have an increased risk of gastro‐oesophageal reflux disease; however, the mechanism underlying this association is uncertain. Aim To test the hypothesis that mechanical effects of obesity on oesophageal function increase acid exposure and symptoms. Methods Height, weight and waist circumference (WC) were measured in patients with typical reflux symptoms referred for manometry and 24 h ambulatory pH studies. Symptom severity was assessed by questionnaire. The association between obesity [WC, body mass index (BMI)], oesophageal function, acid exposure and reflux symptoms was assessed. Results Physiological measurements were obtained from 582 patients (median age 48, 56% female) of whom 406 (70%) completed symptom questionnaires. The prevalence of general obesity was greater in women (BMI ≥ 30 kg/m2; F 23%:M 16%; P = 0.056), however more men had abdominal obesity (WC ≥ 99 cm (M 41%:F 28%; P = 0.001)). Oesophageal acid exposure increased with obesity (WC: R = 0.284, P < 0.001) and was associated also with lower oesophageal sphincter (LOS) pressure, reduced abdominal LOS length and peristaltic dysfunction (all P < 0.001). Univariable regression showed a negative association of WC with both LOS pressure and abdominal LOS length (R = −0.221 and −0.209 respectively; both P < 0.001). However, multivariable analysis demonstrated that the effects of increasing WC on oesophageal function do not explain increased acid reflux in obese patients. Instead, independent effects of obesity and oesophageal dysfunction on acid exposure were present. Reflux symptoms increased with acid exposure (R = 0.300; P < 0.001) and this association explained increased symptom severity in obese patients. Conclusions Abdominal obesity (waist circumference) is associated with oesophageal dysfunction, increased acid exposure and reflux symptoms; however, this analysis does not support the mechanical hypothesis that the effects of obesity on oesophageal function are the cause of increased acid exposure in obese patients.